PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Dian Arsy Syafira; M. Barkah Salim; Eko Prihandono (Universitas Muhammadiyah Metro, 2025)
Abstract: The purpose of this study was to determine the application of problem based learning can improve problem solving skills This study used classroom action research, using 2 research cycles with each cycle being implementation, application, observation, and reflection. The research instruments used were lesson plans, and student worksheets. The implementation of learning is done through five stages. Stage 1: Directing students to the problem, stage 2: Organizing students during the learning process, stage 3: Assisting independent and group investigations, stage 4: Developing and presenting work and exhibitions, stage 5: Evaluating and reflecting on the learning process. This application has assessment results taken from the value of student worksheets in cycle I is 75.00, 81.25, and 87.50 with each of these values then included in the good category. Whereas in cycle II the values were 87.50 and 93.25 in the very good category. The application of problem-based learning can improve the problem solving ability of students in class XI IPA SMA Muhammadiyah 2 Metro on light waves material in the form of understanding problem-based concepts.